Estimation of current population status of the Alcon large blue Phengaris alcon (Denis & Schiffermüller, 1775) (Lepidoptera: Lycaenidae) in Bela krajina (SE Slovenia) based on egg counts - Ivan Kljun; Tjaša Zagoršek; Tadeja Rome; Tanja Lončar; Barbara Ramšak (Natura Sloveniae)
An estimate of population size of the endangered Alcon large blue (Phengaris alcon) in Bela krajina (SE Slovenia) was performed based on egg counts. The presence of eggs has been confirmed in all seven currently known populations of the larval host plant Gentiana pneumonanthe in the area. Owing to the short distances between the populations it is probable that the species forms a single metapopulation with an estimated population size of about 190 individuals. One local extinction is documented on a site where P. alcon was present in 2008. We propose conservation measures to preserve the existence of P. alcon in Bela krajina.